Pengaruh Media Flashcard Terhadap Keterampilan Membaca Permulaan Mata Pelajaran Bahasa Indonesia Kelas 1 UPTD SDN 214 Inpres Bawalangiri - Abdul Rifai; Amal Akbar; Akbar Avicenna (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The main problem in this study is the influence of flash card media on the results of reading skills of grade 1 students of UPTD SDN 214 Inpres Bawalangiri. This study aims to describe the Influence of Flash Card Media on Beginning Reading Skills for the Indonesian Language Subject for Grade 1 UPTD SDN 214 Inpres Bawalangiri. This type of research is quantitative research that uses experimental research (pre-experimental design) with a one-group pretest-posttest design. The population in this study were all grade 1 students of UPTD SDN 214 Inpres Bawalangiri with a sample size of 31 students. The research instruments used in collecting data were tests (pretest-posttest) and observation sheets. The data analysis technique used in this study used descriptive statistical analysis and inferential statistical analysis with the t-test. The results of the study prove that there is an influence of reading skills with flash card media on grade 1 students of UPTD SDN 214 Inpres Bawalangiri.